The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1021/bi0273213
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian 5-Formyluracil−DNA Glycosylase. 2. Role of SMUG1 Uracil−DNA Glycosylase in Repair of 5-Formyluracil and Other Oxidized and Deaminated Base Lesions

Abstract: In the accompanying paper [Matsubara, M., et al. (2003) Biochemistry 42, 4993-5002], we have partially purified and characterized rat 5-formyluracil (fU)-DNA glycosylase (FDG). Several lines of evidence have indicated that FDG is a rat homologue of single-strand-selective monofunctional uracil-DNA glycosylase (SMUG1). We report here that rat and human SMUG1 (rSMUG1 and hSMUG1) expressed from the corresponding cDNAs indeed excise fU in single-stranded (ss) and double-stranded (ds) DNA. The enzymes also excised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 40 publications
(69 reference statements)
5
107
1
1
Order By: Relevance
“…Regarding a potential role for other glycosylases in the excision of fC and caC, it has been shown that SMUG1 cannot remove fC from DNA (46). We find that MBD4 (catalytic domain) has ϳ120-fold lower activity for G⅐fC relative to a G⅐T substrate and that G⅐fC activity is ϳ450-fold lower for MBD4 as compared with TDG.…”
Section: Discussionmentioning
confidence: 70%
“…Regarding a potential role for other glycosylases in the excision of fC and caC, it has been shown that SMUG1 cannot remove fC from DNA (46). We find that MBD4 (catalytic domain) has ϳ120-fold lower activity for G⅐fC relative to a G⅐T substrate and that G⅐fC activity is ϳ450-fold lower for MBD4 as compared with TDG.…”
Section: Discussionmentioning
confidence: 70%
“…The structure of human UDG and that bound to uracil-containing oligo has demonstrated the basis for the enzyme-assisted nucleotide flipping [21,22]. Another DNA glycosylase SMUG1 has been characterized 30 npg in human cells [23,24], which catalyzes excision of U and also oxidized pyrimidines such as 5-hydroxycytosine (5-OHC). SMUG1 is a member of UDG family of glycosylases.…”
Section: Dna Glycosylase a Key Enzyme In Bermentioning
confidence: 99%
“…Although it has been suggested that hmdC may be removed by a mammalian DNA glycosylase (12), the identity of this glycosylase is unknown. However, deamination of hmdC yields 5-hydroxymethyl-uracil (hmdU), a substrate for SMUG1, TDG, and MBD4 (64), suggesting that the hmdC lesion may be cleared from genomic DNA by deamination followed by BER. In addition to lesions formed by direct oxidative damage to DNA from ROS, chronic induction of ROS promulgates a host of cellular alterations, including significantly elevated levels of LPO (5).…”
Section: Oxidative Base Damage Repaired By Bermentioning
confidence: 99%